Historical Context of Cardiac Rehabilitation: Learning From the Past to Move to the Future - Redfern, Julie; Gallagher, Robyn; O’Neil, Adrienne; Grace, Sherry L.; Bauman, Adrian; Jennings, Garry; Brieger, David; Briffa, Tom (Frontiers in Cardiovascular Medicine, 2022)
Contemporary myocardial infarction (MI) care and management has evolved dramatically since the 1950’s; yet outpatient rehabilitation remains underutilized. Understanding the historical context underscores the need to reform policy and practice related to secondary prevention of coronary disease in light of societal changes as well as medical, digital and surgical advancements. Contemporary ‘cardiac rehabilitation’ began when bed rest and physical inactivity was recommended and commonplace for MI survivors. Today, most patients who survive an MI, undergo reperfusion therapy, a short inpatient stay and are discharged with minimal physical morbidity. Despite this, most cardiac rehabilitation programs continue to follow the traditional outpatient model that is incongruent with the contemporary context, especially in the COVID-19 era. This review aims to describe the historical foundations of cardiac rehabilitation to inform solutions and meet the demands of contemporary MI management. Delivering health systems reform to address modernization is a major challenge for current healthcare and requires a unified, efficient, and multidisciplinary approach.